III situ Degradability of Mesquite Pods and the Effect of Urea Supplementation in Sheep - Sharma, T; Purohit, G R; Mathur, B K (Annals of Arid Zone, 2016)
In sitl/ degradability of urea supplemented processed mesquite pods containing 91.76% OM, 12.16% CP, 3.48% EE, 24.73% CF, 52.53% NFE, 7.10% TA and 92.90% OM were determined in three adult fistulated rams, using polyester bag technique. Three urea levels were used, viz., 0% (Pl-OU), 1%. (Pl-I U) and 2% (Pl-2U) to supplement for processed mesquite pods to determine their effect on degradability of dry matter, nitrogen and organic matter as affected by urea supplementation. The dry matter and organic matter degradability increased from 6 to 72 hours with faster rate of degradation in early hours of incubation i.e., 6, 12 and 24 h. Urea supplementation did not show any clear cut effect on these degradabilities. Nitrogen degradability also showed rapid disappearance up to 24 h and thereafter rate of increase up to 72 h was slow but the effect of urea was significant and the nitrogen degradation was rapid initially, particularly at 6 h of incubation. The overall mean OM, N and OM degradabilities of mesquite pods without urea (Pl-OU) were 63.97±1.33, 68.70±3.68 and 62.04±1.94%, respectively. The ROP value of Pl-OU, Pl-IU and Pl-2U were found to be 57.31, 63.18 and 67.48%, respectively.